Gendered Entrepreneurship Contextualization in Egypt: An Empirical Study on Policies for Women Entrepreneurship Empowerment - El-Fiky, Sarah (AUC Knowledge Fountain, 2021)
The proportion of women entrepreneurs has increased dramatically over the past decade, not just in the developed world but also in developing countries. This led to a significant increase in the governments’ attention towards designing and implementing female-focused policies to allocate adequate resources for empowering women entrepreneurs in Egypt. This paper examines one main question: How does the Egyptian government empower women entrepreneurs through key policy interventions? This is only possible through testing the proposed research hypotheses and investigating Egypt’s publicized policies and governmental interventions. Based on a gender-lens perspective, this research tries to close the gaps in previous research and determine the impact of systematic gendered policies on empowering women entrepreneurship and, in return, aid in the overall economic growth and development nation-wide. This paper starts with foundational quantitative research that is later enriched with qualitative research by employing mixed methods research mode. The data was then triangulated, and the empirical results indicated the gender empowerment direction adopted by the Egyptian government, which is apparent in several reports addressing the SDGs and Egypt’s cooperation with different international and national non-governmental organizations on gender fronts. Nonetheless, it was also indicated that the results have yet to be realized from such publicized efforts and policies. Finally, the findings highlight the main challenges that the government portrays for women entrepreneurs, including the gridlock where government reports publicize new programs and more support for women entrepreneurs, while results indicated the minimal resources provided to a little number of women entrepreneurs.